2020
DOI: 10.1017/s1368980020002888
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of low dairy calcium intake and association with insomnia, anxiety, depression and musculoskeletal pain in university students from Jordan

Abstract: Objective: To assess dairy Ca intake and investigate its relationship with insomnia and other common co-morbidities including anxiety, depression and musculoskeletal pain (MSP) among university students. Design: Cross-sectional study. Setting: University, Irbid, Jordan. Participants: Male and female individuals (n 1000), aged 20·87 ± 2·69 years. Results: Low dairy Ca intake (<1000 mg/d) was reported by 96·5 % of participants, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Furthermore, in the current study the participants who were divorced/widowed they have 3.09 times higher risk or probability of experiencing insomnia. This results support with many publish research ( Necho et al, 2020 , Alkhatatbeh et al, 2020 , Al Karaki et al, 2020 ). Our study also reported that those medical clinical students living in hostels during the COVID pandemic they have more insomnia (1.23 times higher) as compared to others variables.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in the current study the participants who were divorced/widowed they have 3.09 times higher risk or probability of experiencing insomnia. This results support with many publish research ( Necho et al, 2020 , Alkhatatbeh et al, 2020 , Al Karaki et al, 2020 ). Our study also reported that those medical clinical students living in hostels during the COVID pandemic they have more insomnia (1.23 times higher) as compared to others variables.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 94.7% had MSP, 84.3% had anxiety, 66.7% had depression, and 66.6% of participants had less than ¼ of recommended amount of daily calcium intake ( 29 ). Previously, High prevalence of low dairy calcium intake and association with insomnia, anxiety, depression and MSP in university students from Jordan was reported ( 17 ). Participants with moderate to severe insomnia had lower dairy calcium, higher anxiety and depression scores and higher measures of MSP compared to participants with no insomnia (P-values < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A dairy serving was defined as: 1 cup of milk or yogurt (300 mg calcium), 2 full table spoons (2 oz.) of labnah (100 mg calcium), and a 1-ounce piece of cheese (162 mg calcium), and cream cheese (20 mg calcium) ( 8 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature (35,(45)(46)(47)(48)(49)(50) and clinical practical implications we used the following covariates, including age, sex, race and ethnicity, education level, PIR, BMI, marital status, diabetes, hypertension, severe CVD, cancer/malignancy, total energy intake, carbohydrate intake, caffeine intake, serum Ca, Ca supplements, smoking status, alcohol consumption status, and physical activity. We divided the participants into five racial and ethnic groups.…”
Section: Covariates Assessmentmentioning
confidence: 99%